Stigma Tuberkulosis Paru di Asia Tenggara: Systematic Literatur Review - Pradana, Tasya Lukita Cyndi; Widjaja Putra, Bayu Taruna; Utami, Wiwien Sugih (Universitas Malahayati, 2025)
ABSTRACT Pulmonary tuberculosis is an infectious disease that remains a global health problem. Tuberculosis stigma is determinants of this disease. The purpose of this study was to find out the determinants of tuberculosis stigma in 4 Southeast Asian regions, namely Thailand, Cambodia, Vietnam and Indonesia. The research method used was a systematic literature review using PRISMA guidelines. From the 14 articles reviewed, it was found that tuberculosis stigma can be divided into two things, namely personal and negative views of the surrounding community. The impact of stigma is that patients choose to isolate themselves, feel embarrassed, and are discriminated against by the surrounding community. The stigma of tuberculosis in four regions make the problem of tuberculosis tend to be high. The author recommends providing education to communities that stigmatize tuberculosis patients. By providing education, the author hopes that the community can change their mindset and provide social support to tuberculosis patients. Keywords: Tuberculosis Stigma, Systematic Literatur Review, Southeast Asia. ABSTRAK Tuberkulosis paru merupakan penyakit menular yang masih menjadi masalah kesehatan di seluruh dunia. Salah satu faktor determinan dari penyakit ini dan adalah stigma tuberkulosis. Tujuan dari penelitian ini mencari tahu faktor determinan stigma tuberkulosis di 4 wilayah Asia Tenggara yaitu Thailand, Kamboja, Vietnam, dan Indonesia. Metode penelitian yang digunakan adalah systematic literatur review dengan pedoman PRISMA. Dari 14 artikel yang direview didapatkan bahwa stigma tuberkulosis dibedakan menjadi dua hal yaitu personal dan pandangan negatif masyarakat sekitar. Dampak yang ditimbulkan dari stigma yaitu pasien memilih untuk mengisolasi diri, merasa malu, dan terdiskriminasi dari lingkungan sekitar. Adanya stigma tuberkulosis di empat wilayah tersebut menjadikan masalah tuberkulosis cenderung tinggi. Penulis merekomendasikan pemberian edukasi pada masyarakat yang memberikan stigma kepada pasien tuberkulosis. Dengan adanya upaya pemberian edukasi, penulis berharap masyarakat dapat merubah pola pikir dan memberi dukungan sosial kepada pasien tuberkulosis. Kata Kunci: Stigma Tuberkulosis, Systematic Literatur Review, Asia Tenggara